(3HjGf GdeUGOQI GdeTghQI ddMceGAs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s ((3YHOGdcGai Hf YHOGdeLjO GdJHQjRi s)
(3ChdgG (B:s
(3HYO MeO ejjQ cd YSjQ Ef GdJYdjeGJ hNUhUkG GdgfOSGJ eY hVhM eSGdcgG s
(3BNQgG (B:s
(3agPG eGJbQQ di gPg GdeSCdI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B924 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B21 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs